2014
DOI: 10.1007/s40167-014-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural asymmetries on the greyscales task: The influence of native reading direction

Abstract: Reliable leftward attentional and perceptual biases demonstrated in a variety of visuospatial tasks have been found to deviate from the left in research examining the influence of scanning habits. The aim of the current research was to examine the influence of native script direction on pseudoneglect during the greyscales task in a representative sample of native right-to-left readers. Fifty-four native left-to-right readers and 43 right-to-left readers completed the greyscales task, which required judging the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…The greyscales task (GRE) requires a comparative luminance (“darkness”) judgement to be made between two parallel horizontal lines containing a mirror-imaged linear contrast gradients ( Fig 1c ). The bar in which the dark section is located on the left side of space tends to be perceived as darker overall, compared to when it is placed on the right [ 10 , 36 41 ]. Most importantly, the left side is reported darker even when the bars are equiluminant, indicating a perceptual overestimation of the darkness of the left side of the stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…The greyscales task (GRE) requires a comparative luminance (“darkness”) judgement to be made between two parallel horizontal lines containing a mirror-imaged linear contrast gradients ( Fig 1c ). The bar in which the dark section is located on the left side of space tends to be perceived as darker overall, compared to when it is placed on the right [ 10 , 36 41 ]. Most importantly, the left side is reported darker even when the bars are equiluminant, indicating a perceptual overestimation of the darkness of the left side of the stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, both RTL and LTR readers showed a bias to report a darker gradient with the dark edge located to the left (Nicholls & Roberts, 2002). However, in another experiment with a larger sample of subjects, RTL readers showed a weaker leftward bias in comparison to LTR readers (Friedrich & Elias, 2014). Furthermore, comparing viewing behavior over images that have a different direction of illumination, Smith and Elias (2013) reported that LTR readers fixated more to the left side of the images in contrast to RTL readers fixating more to the right.…”
Section: Experiments 1a and B: The Influence Of Reading Direction On Tmentioning
confidence: 91%
“…This rules out a possibility suggested by a reviewer, that participants could only identify one letter on any one trial, but attended to one side in some trials and the other side in the remaining trials. 65; with stream F(1,23) = .03, p = .86; with both for the three-way interaction F (3,69) = .92, p = .44).…”
Section: Methodsmentioning
confidence: 90%
“…A smaller study with a related grayscales task (Mattingley et al, 1994) did not find a significant difference between native English readers and readers whose main language was Hebrew, although a consistent trend is evident in the data (Nicholls & Roberts, 2002). A recent study with a larger sample of right-to-left readers found a significant right bias in the right-to-left readers (Friedrich & Elias, 2014). These findings question the usual interpretation of left biases in terms of an intrinsic right-hemisphere advantage (e.g.…”
mentioning
confidence: 80%